Optimization of Microwave Treatment to Improve Adsorption Properties of Porous Rice Starch - Elok Pawening Maharani; Priyanto Triwitono; Yudi Pranoto; Djagal Wiseso Marseno (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Porous starch (PS) is used in various foods as a flavoring, absorbent, and to protect vitamins and oils. Rice starch is processed to minimize the preparation time of PS, while simultaneously maintaining its adsorption efficiency. This study aims to optimize microwave treatment to improve the water, oil, and methylene blue adsorption capacity and PS yield of rice. This study used Response Surface Methodology (RSM) with Central Composite Design (CCD) to optimize the water, oil, and methylene blue adsorption capacity and PS yield of rice. Two factors were considered: time (X₁: 3-15 s) and power (X₂: 100-200 W/g). The statistical significance of the responses was evaluated using analysis of variance (ANOVA) at the 95% confidence level, with differences considered significant at p<0.05. Linear and quadratic models were the modes suggested by the software. Model analysis showed that microwave time and power significantly affected the adsorption properties. Based on the research results, the optimum conditions for making porous rice starch were obtained by using a microwave time of 15 s and a power of 171 W/g, resulting in a water absorption capacity of 96.34±2.93%, an oil absorption capacity of 142.85±0.94%, a methylene blue absorption capacity of 34.73±5.67%, and a yield of 95.26±3.23%.